Sarcopenia‐related changes in serum GLP‐1 level affect myogenic differentiation - Hsien‐Hao Huang; Y.B. Zhang S.H. Wang; Hui‐Yu Jiang; Helen Yu; Yin‐Quan Chen; Arthur Chiou; Jean‐Cheng Kuo (2024)
Sarcopenia, a group of muscle-related disorders, leads to the gradual decline and weakening of skeletal muscle over time. Recognizing the pivotal role of gastrointestinal conditions in maintaining metabolic homeostasis within skeletal muscle, we hypothesize that the effectiveness of the myogenic programme is influenced by the levels of gastrointestinal hormones in the bloodstream, and this connection is associated with the onset of sarcopenia.